1996
DOI: 10.1046/j.1365-2265.1996.8510861.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating inhibins and activin A during GnRH‐analogue down‐regulation and ovarian hyperstimulation with recombinant FSH for in‐vitro fertilization‐embryo transfer

Abstract: These results indicate that ovarian production of dimeric inhibin A and B are gonadotrophin dependent, whereas activin A may have a significant gonadotrophin independent or extra-gonadal source. Inhibin A and pro alpha C may be useful markers for monitoring the effects of gonadotrophin stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
2
4

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(30 citation statements)
references
References 26 publications
2
22
2
4
Order By: Relevance
“…This pattern indicates that there may be a close correlation between FSH and activin A. This observation is in contrast to our ®nding that activin A levels fell due to the short FSH pulses during GnRH stimulation, and the observation of Lockwood et al (28) that activin A levels remained unchanged in conjunction with the fall of FSH levels when long-term GnRH analogues were administrated to downregulate the hypophysis. This suggests that the production of activin A is not regulated by FSH.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…This pattern indicates that there may be a close correlation between FSH and activin A. This observation is in contrast to our ®nding that activin A levels fell due to the short FSH pulses during GnRH stimulation, and the observation of Lockwood et al (28) that activin A levels remained unchanged in conjunction with the fall of FSH levels when long-term GnRH analogues were administrated to downregulate the hypophysis. This suggests that the production of activin A is not regulated by FSH.…”
Section: Discussioncontrasting
confidence: 56%
“…Moreover, our investigation of the response of pro alpha-C to GnRH downregulation produced different results than those described in the Lockwood et al study (28). Before stimulation with recombinant FSH for in vitro fertilization (IVF) Lockwood et al (28) measured unaltered pro alpha-C concentrations after pituitary downregulation with GnRH.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Unfortunately, more detailed analyses concluded that early follicular phase inhibin B serum levels are only of limited value in predicting response during ovarian hyperstimulation (18 -21). Dynamic inhibin B testing with FSH stimulation (22,23) or gonadotropin releasing hormone (GnRH) agonist administration (24) appears to correlate better with ovarian response. A good correlation was also observed between inhibin B concentrations during ovarian hyperstimulation and the number of oocytes retrieved (25,26).…”
Section: Introductionmentioning
confidence: 99%
“…Inhibin B was suggested as an early sensitive predictor of ovarian reserve (Seifer et al, 1997;. With better understanding of the control of synthesis and secretion of the inhibins and their potential endocrine role in the menstrual cycle, attention has turned to the possibility of this family of peptides to provide a more direct index of ovarian reserve and an improved predictor of ART outcome (Hughes et al, 1990;Groome et al, 1994;Balasch et al, 1996;Lockwood et al, 1996;Seifer et al, 1997;Danforth et al, 1998;Corson et al, 1999;Hall et al, 1999;Peñarrubia et al, 2000;Laven and Fauser, 2004;Shanthi et al, 2004).…”
Section: Introductionmentioning
confidence: 99%